A major practicum report for Celebes Canning Corporation Bo. Cabu, Tambler, General Santos City - Caalim, Japhil Sumawang (2007)
As part of the curriculum of the Bachelor of Science in Food Technology, a 288 hours of plant practice was conducted at Celebes Canning Corporation from April to May 2006. The plant practice aimed to provide the intern with adequate exposure and training as a quality assurance checker on the different activities in the tuna processing line. Through the plant practice, the intern was able to apply all the relevant insights she learned from the academe. She was able to gather necessary information about the plant including the company profile and organizational structure, its mission, vision, production and processing systems and the protocols implemented to achieve high product quality and to ensure food safety. This manuscript is made to document the intern?s experience during the plant practice and to present a comprehensive technical analysis on the different process operations in a tuna canning plant